Potential anti-tumor activites of extract from fresh leaves of the male papaya (Carica papaya L.) collected in Ha Tinh province - Phuong Trinh, Tran; Bao Linh, Phan; Tam, Pham Thi (Vietnam Journal of Biotechnology, 2020)
Nowadays, the percentage of people with cancer is increasing. There are many methods used to treat cancer such as surgery, chemotherapy, the radiation, etc. In addition, the use of medicinal plants, natural products, is also popularly applied for cancer patients. Using 90% ethanol as the extraction solvent, we produced 4 kinds of concentrated extracts from dried flowers, dried leaves, fresh flowers, fresh leaves of male papaya (Carica papaya Linn). In vitro study, the extracts of dried flowers, fresh flowers did not effect on MCF7, A549, HT 29, Huh 7R, HEK 293 and LLC cancer cell lines. The extracts of dried leaves and fresh leaves presented cytotoxic effects with IC50 values ranging from 1.88 to 13.64 mg/mL. Meanwhile, activities of the extract of fresh leaves was 4-6 times stronger than that of the extract of dried leaves's. Based on evaluation of the IL2 and IL6 production capability of macrophage, we found that the extract of fresh leaves strongly inhibited the IL-6 production at 4 mg/mL (50.56%) and 0.8 mg/mL (23.79%) in comparison with the negative control (P<0.05) while it did not show the ability to induce IL-2 in the same studied concentrations. Using tumor bearing mice as model for studying the antitumor activities of extract of fresh leaves at the dose of 3 mL/kg/day and 6 mL/kg/day, we identified the positive effects of the higher dose treatment. The results showed that the extract of fresh leaves at the dose of 6 mL/kg/day could inhibit 33.44% the tumors’ sizes on day 28 (P<0.05); tumor's weigh decreased to 9.84 against 13.76 g of the negative control; the WBC parameter reduced from 41.65x106/mL to 19.1x106/mL (P<0.05), AST decreased from 1441.6 U/L to 1038.97 U/L (P<0.01), and creatinin decreased from 26.37 µmol/L to 20.63 µmol/L compared with the negative control group (P<0.05). These promising results are the scientific evidences for applying this extract in cancer treatment in the future.